Pliocene Indonesian Throughflow and Leeuwin Current dynamics: Implications for Indian Ocean polar heat flux - Karas, Cyrus; Nürnberg, Dirk; Tiedemann, Ralf; Garbe-Schönberg, Dieter (Paleoceanography, 2011)
To understand the gradual global cooling during the mid-Pliocene (3.5–2.5 Myr ago) one needs to consider the tectonical constriction of tropical seaways, which affected ocean circulation and the evolution of climate. Here we use paired measurements of δ18O and Mg/Ca ratios of planktonic foraminifera to reconstruct the Pliocene hydrography of the western tropical Indian Ocean (Site 709C) and changes in the Leeuwin Current in the eastern subtropical Indian Ocean (Site 763A) in response to Indonesian Gateway dynamics. Today, the Indonesian Throughflow (ITF) and, subsequently, the warm southward flowing Leeuwin Current off Western Australia are essential for the polar heat transport in the Indian Ocean. During 3.5–3 Ma, sea surface temperatures significantly dropped in the Leeuwin Current area, becoming since ~3.3 Ma 2°C–3°C cooler than the rather unchanged sea surface temperatures from the eastern and western tropical Indian Ocean. We refer this drop in sea surface temperatures to a weakened Leeuwin Current with severe climatic effects on Western Australia induced by a tectonically reduced surface ITF. We suggest that this reduced surface ITF led to a diminished poleward heat transport in the Indian Ocean resulting in a weakened Leeuwin Current and possibly to cooling of the Benguela upwelling system.